1976
DOI: 10.1017/s0025315400020488
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum compounds in the marine food web: short-term experiments on the fate of naphthalene in Calanus

Abstract: Adult female Calanus helgolandicus Claus immersed for 24 h in sea-water solutions of [1-14C]naphthalene accumulated a detectable quantity (3.6 pg/animal) from concentrations as low as 0.10 μg/1.Feeding experiments using barnacle nauplii or diatoms as foods showed that the dietary route of entry was more important quantitatively than direct uptake from solution in that in order to ensure that the same quantity of radioactivity in the animals was attained by the two routes the level of hydrocarbon in solution ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 13 publications
(18 reference statements)
2
24
0
1
Order By: Relevance
“…(197.6) found uptake of BP in larval blue crab to be more efficient from food than from water. and Corner et al (1976) found similar results for uptake of naphthalene in Calanus. Dobrosky and Epifanio (1980) however, found the opposite trend for BP accumulation in larval bivalves.…”
Section: Biological and Eheaical Availability Of Parsupporting
confidence: 65%
See 1 more Smart Citation
“…(197.6) found uptake of BP in larval blue crab to be more efficient from food than from water. and Corner et al (1976) found similar results for uptake of naphthalene in Calanus. Dobrosky and Epifanio (1980) however, found the opposite trend for BP accumulation in larval bivalves.…”
Section: Biological and Eheaical Availability Of Parsupporting
confidence: 65%
“…Sanborn and Ma lins (1977) found that in vivo metabolism of naphthalene by larval spot shrimp was affected by complexation of the PAR with bovine serum albumin. Corner et al (1976) reported differences in accumulation and metabolism of naphthalene from the water column or from dietary sources by the copepod Calanus.…”
Section: Determination Of Glucuronide and Sulfate Conjugates In Aqueomentioning
confidence: 99%
“…In earlier experimental studies, it was found that the marine copepods typically had a low retention of PAHs. For example, the copepods lost > 35% of naphthalene accumulated from the food over the 24 h depuration period (Corner et al 1976, Harris et al 1977a. Furthermore, the slow intracellular accumulation of BaP by phytoplankton may affect the interpretation of the AE experiments in which phytoplankton were labeled for 2 h before fed to copepods.…”
Section: Discussionmentioning
confidence: 99%
“…Marine copepods are the link between the primary producers and the higher trophic level such as fish, thus uptake by zooplankton presents another redistribution pathway for organic contaminants in the marine food chains. The bioaccumulation of PAHs by zooplankton has been considered in only a few early studies (Corner et al 1976, Harris et al 1977a. Fundamental processes of PAH transport in the lower trophic food chain need to be better understood to enable prediction of the environmental fate and food chain transport in the ecosystem of concern.…”
Section: Introductionmentioning
confidence: 99%
“…The range of WSF concentrations used in the present work has, however, specifically been chosen to investigate the sub-lethal effects related to natural background concentrations of pollutants (Ohwada et al, 2003;Hashim, 2010). More specifically, among those compounds, BTEX are the main class of hydrocarbons found in WSF (Carls & Rice, 1990;Saeed & Al-Mutairi, 1999), and naphthalene is one of the most abundant polycyclic aromatic hydrocarbons dissolved in oil contaminated waters (Corner et al, 1976) and has been widely used in toxicological assays (Corner et al, 1976;Berdugo et al, 1977;Calbet et al, 2007). BTEX and naphthalene concentrations are respectively in the range 450-35000 g l -1 and 30-26000 g l -1 in 100% water-soluble fraction (Saeed & AlMutairi, 1999;Rodrigues et al, 2010).…”
Section: Hydrocarbon Contaminant: the Water-soluble Fraction Of Diesementioning
confidence: 99%